2017
DOI: 10.1080/09500340.2017.1357853
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthally unidirectional transport of energy in magnetoelectric fields: topological Lenz’s effect

Abstract: Magnetic-dipolar modes (MDMs) in a quasi-2D ferrite disk are microwave energyeigenstate oscillations with topologically distinct structures of rotating fields and unidirectional power-flow circulations. At the first glance, this might seem to violate the law of conservation of an angular momentum, since the microwave structure with an embedded ferrite sample is mechanically fixed. However, an angular momentum is seen to be conserved if topological properties of electromagnetic fields in the entire microwave st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Nontrivial topology of MDM oscillations in such a sample manifests itself in unidirectionally rotating (chiral) eigenmodes. Breaking of symmetry between clockwise and counterclockwise modes due to the chiral boundary conditions results in appearance of MDM angular momenta and power‐flow vortices . We have unidirectionally rotating spin‐wave packet that carries an orbital angular momentum.…”
Section: Me Fields and Quasi‐magnetostatic Quantized Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nontrivial topology of MDM oscillations in such a sample manifests itself in unidirectionally rotating (chiral) eigenmodes. Breaking of symmetry between clockwise and counterclockwise modes due to the chiral boundary conditions results in appearance of MDM angular momenta and power‐flow vortices . We have unidirectionally rotating spin‐wave packet that carries an orbital angular momentum.…”
Section: Me Fields and Quasi‐magnetostatic Quantized Statesmentioning
confidence: 99%
“…This explains the picture of power flow rotations shown in Figure 3. The “source” of the helicity factor is the pseudoscalar quantity of the magnetization distribution in a ferrite disk at the MDM resonances: Vtruem·false(×mfalse)dV0 V is a volume a ferrite sample. These magnetization parameters are distributed asymmetrically with respect to the z ‐axis (see Figure 4).…”
Section: Me Fields and Quasi‐magnetostatic Quantized Statesmentioning
confidence: 99%
“…On a surface of a MDM ferrite disk, there are both the regions of the orbitally driven normal magnetic and normal electric fields. Moreover, the maximums (minimums) of the electric and magnetic fields normal to the disk are situated at the same places on the disk plane [36]. When a metal wall is placed closely to a ferrite-disk plane, this field structure is projected on the metal.…”
Section: Ss Hjmentioning
confidence: 99%
“…In Ref. [36] it was shown that due to the topological action of the azimuthally unidirectional transport of energy in a MDM-resonance ferrite sample there exists the opposite topological reaction (opposite azimuthally unidirectional transport of energy) on a metal screen placed near this sample. This effect is called topological Lenz's effect.…”
Section: Ss Hjmentioning
confidence: 99%
See 1 more Smart Citation